Estudio de prefactibilidad para la implementación de una planta de elaboración de biotextil de látex de shiringa (Hevea brasiliensis) - Torres Anyosa, Camila Lisseth (2022)
The study about the pre-feasibility of a biotextile production plant from shiringa latex, commercially known as "vegetal leather", seeks to evaluate and determine the economic, social and technological viability of a sustainable proposal applicable to the fashion sector. The plan is to develop an industrial process that presents an alternative material to animal leather, in order to achieve mitigation of the environmental and social impact that is currently generated by the tannery sector. This is driven by a change of the consumer who is buying more consciously, in whose decision is prevailing the quality and impact of the acquisition, which is causing an increase in the demand for sustainable products. To carry out the study, interviews with experts in the tannery sector and sustainable fashion sector were conducted, as well as interviews to entrepreneurs related to the production of similar materials to the one proposed. On the other hand, the research is based on the demand for animal leather, due to the fact that the syringa latex biotextile is presented as a substitute product, and because the proposal is part of the so-called "sustainable leathers", which have little time of appearance in the market, which is why studies on this sector are still in development. The study will touch points such as the determination of the value proposition, a market study that will indicate the potential demand and segmentation based on the experience of industry related entrepreneurs, who take into account consumption patterns of final customers. It will also carry out an analysis of the offer, that will allow defining the form of marketing and distribution of the product, and then continue with a study of the plant location.